2020
DOI: 10.1111/echo.14663
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic principles of prosthetic aortic valve evaluation in the transcatheter aortic valve replacement era

Abstract: Evaluating the hemodynamic performance of aortic valve prostheses has relied primarily on echocardiography. This involves calculating the trans-prosthetic valve mean gradient (MG) and aortic valve area (AVA), and assessing for valvular and paravalvular regurgitation in a fashion similar to the native aortic valve. In conjunction with other echocardiographic and nonechocardiographic parameters, MG and AVA are used to distinguish between prosthesis stenosis, prosthesis patient mismatch, pressure recovery, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
1
23
1
Order By: Relevance
“…Discordance between echocardiography and catheterization in the assessment of transvalvular mean gradient has been reported in native aortic stenosis (AS), following SAVR, TAVR, and ViV-TAVR. 2 Echocardiography overestimates the invasive mean gradients, and previous studies have suggested that following SAVR, this discordance is related to valve design [3][4][5][6] and degree of prosthesis obstruction, 7 and it is independent of the aortic dimension and the phenomenon of pressure recovery. 2 The relationship between echocardiography and catheterization mean gradients has not been investigated in patients with degenerate bioprosthetic valves.…”
Section: See Commentary On Page 61mentioning
confidence: 95%
See 4 more Smart Citations
“…Discordance between echocardiography and catheterization in the assessment of transvalvular mean gradient has been reported in native aortic stenosis (AS), following SAVR, TAVR, and ViV-TAVR. 2 Echocardiography overestimates the invasive mean gradients, and previous studies have suggested that following SAVR, this discordance is related to valve design [3][4][5][6] and degree of prosthesis obstruction, 7 and it is independent of the aortic dimension and the phenomenon of pressure recovery. 2 The relationship between echocardiography and catheterization mean gradients has not been investigated in patients with degenerate bioprosthetic valves.…”
Section: See Commentary On Page 61mentioning
confidence: 95%
“…2 Echocardiography overestimates the invasive mean gradients, and previous studies have suggested that following SAVR, this discordance is related to valve design [3][4][5][6] and degree of prosthesis obstruction, 7 and it is independent of the aortic dimension and the phenomenon of pressure recovery. 2 The relationship between echocardiography and catheterization mean gradients has not been investigated in patients with degenerate bioprosthetic valves. We sought to compare echocardiographic and invasive mean gradients in patients with failed surgical bioprosthesis.…”
Section: See Commentary On Page 61mentioning
confidence: 95%
See 3 more Smart Citations